Analisis Pengembangan Kurikulum Muatan Lokal Kewirausahaan - Thohir, M. Mahrus (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2022)
This article describes the local content curriculum for entrepreneurship applied at MA Al-Khidmah Ngronggot which is basically in order to prepare graduates to have the skills to develop student creativity and also train students to be independent in dealing with all the problems that will be faced after graduating from school, especially in terms of The focus of research in this article includes, a) Development of the Entrepreneurship Local Content Curriculum at MA Al-Khidmah Ngronggot using the 2013 curriculum, b) The practice of developing the entrepreneurial spirit of students through the development of a local content curriculum at MA Al-Khidmah Ngronggot, c) Inhibiting factors and Supporting Entrepreneurship Local Content Curriculum Development at MA Al-Khidmah Ngronggot For factors supporting the development of entrepreneurship local content curriculum. The research method in the article is qualitative. As directed by the type of qualitative research, the collected data is analyzed with the provision of intellectual weapons in the form of theory as presented in chapter II to obtain various interpretive descriptions according to logical and rational scientific research principles. Keywords: Curriculum, Local Content, Entrepreneurship